Study of motor units of M. pectineus of the dog (Canis familiaris) - Guazzelli Filho, J.; De Carvalho, V. C.; Dall Pai, V. (My University, 1986)
Cross sections of M. pectineus of 6 adult dogs were used to study the number of motor units. The authors' results revealed that M. pectineus possesses 29,451 muscle fibres and 165 large nerve fibres. Since 60% of these latter fibres are motor fibres, the number of fibres per motor unit of M. pectineus is 294. This fact suggests that this muscle executes finely adjusted movements.